Treatment of two different water resources in desalination and microbial fuel cell processes by poly sulfone/Sulfonated poly ether ether ketone hybrid membrane - Mostafa, Ghasemi; Wan Ramli, Wan Daud; Javed, Alam; Hamid, Ilbeygi; Mehdi, Sedighi; Ahmad Fauzi, Ismail; Mohammad, H. Yazdi; Saad, A. Aljlil (Elsevier B.V., 2016)
The PS (Polysulfone)/SPEEK (sulfonated poly ether ether ketone) hybrid membranes were fabricated and modified with low and high DS (degrees of sulfonation) for the desalination of brackish water and proton exchange membrane in microbial fuel cell. The results illustrated that SPEEK has changed the morphology of membranes and increase their hydrophilicity. PS/SPEEK with lower DS (29%) had the rejection percentage of 62% for NaCl and 68% for MgSO4; while it was 67% and 81% for PS/SPEEK (76%) at 4 bars. Furthermore, the water flux for PS at 10 bar was 12.41 L m2 h1 . It was four times higher for PS/ SPEEK (29%) which means 49.5 L m2 h1 and 13 times higher for PS/SPEEK (76%) with means 157.76 L m2 h1 . However, in MFC (microbial fuel cell), the highest power production was 97.47 mW/m2 by PS/SPEEK (29%) followed by 41.42 mW/m2 for PS/SPEEK (76%), and 9.4 mW/m2 for PS. This revealed that the sulfonation of PEEK (poly ether ether ketone) made it a better additive for PS for desalination, because it created a membrane with higher hydrophilicity, better pore size and better for salt rejection. Although for the separator, the degree of sulfonation was limited; otherwise it made a membrane to transfer some of the unwanted ions.